2015
DOI: 10.1186/2056-5917-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Getting more efficient Rapid Response System (RRS) utilization by the use of a general ward based deteriorating patient contract

Abstract: Objective: To determine if a general ward-based plan to address the deteriorating patient could improve RRS utilization over and above a mandatory organizational policy and procedure. Design: A two stage methodology: First, engagement with ward providers and users of the RRS to generate ward-based interventions; Second, measurement of the incidence of missed/delayed RRS calls, RRS calls, cardiac arrests and unplanned intensive care unit admission both prior to the intervention and 12 months post implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…(29) Regarding the professionals' lack of adherence to protocols, it was observed that better knowledge and familiarity with the instruments of criteria to evaluate the signs can increase adherence to activation of the teams, avoiding delays. (30) The team's composition may vary for each hospital, and most have a doctor leading the team. The need for the doctor in the RRT as a factor that can interfere with its efficiency is still controversial.…”
Section: Rapid Response Team: What Factors Interfere With Its Performmentioning
confidence: 99%
“…(29) Regarding the professionals' lack of adherence to protocols, it was observed that better knowledge and familiarity with the instruments of criteria to evaluate the signs can increase adherence to activation of the teams, avoiding delays. (30) The team's composition may vary for each hospital, and most have a doctor leading the team. The need for the doctor in the RRT as a factor that can interfere with its efficiency is still controversial.…”
Section: Rapid Response Team: What Factors Interfere With Its Performmentioning
confidence: 99%
“…[10][11][12] Cognitive aids target all 3 key domains associated with the timely recognition and effective management of complications in the surgical population 13 : they improve communication, 14,15 teamwork and leadership, [15][16][17] and the surgical safety culture [17][18][19] and are therefore likely to be effective in decreasing failure to rescue. More specifically, they accelerate escalation of care 20 and optimize resuscitation by reducing the amount of omitted critical treatment steps. 21 To our knowledge, there are no cognitive aids for the management of deteriorating surgical patients.…”
mentioning
confidence: 99%